2013
DOI: 10.1603/me12226
|View full text |Cite
|
Sign up to set email alerts
|

Vector Competence of Argentine Mosquitoes (Diptera: Culicidae) for West Nile virus (Flaviviridae: Flavivirus)

Abstract: We examined the ability of Culex pipiens L. complex mosquitoes from Argentina to vector West Nile virus (WNV) to assess their role in the transmission of WNV in South America. Several egg rafts of Culex spp. were collected from different breeding sites in the suburbs of the city of La Plata, Argentina, and a subset of each progeny was scored with morphological and genetic species indicators. Surprisingly, we did not find Cx. pipiens form pipiens, but found evidence of genetic hybrids of Culex quinquefasciatus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 63 publications
2
35
0
2
Order By: Relevance
“…The same situation accounts for the presence of Cx. pipiens , for which the absence of diapause could indicate the presence of the molestus biotype, which was recently reported by Micieli et al (2013) near the study area.…”
Section: Discussionsupporting
confidence: 71%
“…The same situation accounts for the presence of Cx. pipiens , for which the absence of diapause could indicate the presence of the molestus biotype, which was recently reported by Micieli et al (2013) near the study area.…”
Section: Discussionsupporting
confidence: 71%
“…Recently, Micieli et al (2013) reported the presence of Culex (Cux.) pipiens form molestus Forskal in the Buenos Aires province, whose identity was confirmed by molecular markers (microsatellites).…”
Section: Discussionmentioning
confidence: 99%
“…p. pipiens form molestus occur associated with underground standing water, such as sewers and storm drains, that remain warm year-round, a necessity since this form cannot diapause (Harbach et al 1984). Not surprisingly, in warmer latitudes, such as in southern Europe (Gomes et al 2009(Gomes et al , 2013a, North Africa (Gomes et al 2012), California (Strickman and Fonseca 2012), and in northern Argentina (Micieli et al 2013), aboveground populations of pure Cx. p. pipiens form molestus and/or hybrids with a strong molestus form signature have also been identified.…”
Section: Introductionmentioning
confidence: 99%